9x+(-9x)=-9x+9x

Simple and best practice solution for 9x+(-9x)=-9x+9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+(-9x)=-9x+9x equation:



9x+(-9x)=-9x+9x
We move all terms to the left:
9x+(-9x)-(-9x+9x)=0
We add all the numbers together, and all the variables
9x+(-9x)-0=0
We add all the numbers together, and all the variables
9x+(-9x)=0
We get rid of parentheses
9x-9x=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 2x+3-7=4 | | 7x+2/35=x+8/14 | | 4n,n=2 | | 2x+10=10x+30-4x | | 14+x=-21 | | k/3+50=0 | | 7=-3k-8 | | 2(b+9)=16 | | 7(p-6)=-14 | | -13(x-6)=-5x+2(5x+12 | | -x-21=x+13 | | a+20=2a-10 | | 3(x+10)=54 | | 10y-5=2y+35 | | -2(n+9)=16 | | q/2=28;.q=14 | | -x-18=5x+6 | | X=47(3x)11 | | 2(2y-18)=3y-18 | | -17=8x-3 | | 2(3x-39)=2x-2 | | -3x-6=2x+9 | | 72+(3x+1)+50=180 | | H×k=4 | | -5(c-4)=-3(c-25) | | (2x-5)(3x+2)=6x2-10 | | 4+6x=10x-8 | | x/10=21/7 | | 16=4x-18 | | 16x-7=8x+2+10x-19 | | X.2x=42 | | 35=7n.n=5 |

Equations solver categories